Pooled prevalence and co-occurrence of diarrhea and wasting and its associated factors among children aged 6–24 months in East Africa: Insight from recent demographic health survey: A multilevel analysis - Alemakef Wagnew Melesse; Mahlet Alehegn; Tigabu Kidie (PLoS ONE, 2026)
Background Young children experiencing both diarrhea and wasting (DW) are at increased risk of severe malnutrition, impaired immune function, and greater susceptibility to infections. This dual burden of illness significantly impacts their health, survival, and development. Diarrhea and wasting are often interlinked, with one exacerbating the other, leading to various cycle of malnutrition and frequent infections.in the long term, these conditions contribute to stunted growth delayed cognitive development and decreased survival rates. Given the vulnerability of children aged 6–24 months, addressing the dual burden of diarrhea and wasting is crucial for improving child health outcomes. This study aims to investigate the pooled prevalence and associated factors of diarrhea and wasting multimorbidity (DW) among children aged 6–24 months in East Africa. Methods A pooled prevalence analysis was conducted using data from the Demographic and Health Surveys (DHS) across 11 East African countries, including a total weighted sample of 78,982 children aged 6–24 months. Given hierarchical structure of the DHS data, a multilevel binary logistics regression model was employed to identify significant factors associated with DWM. The Intra-class correlation (ICC), Median odds ratio (MOR), and LogliklihoodRatio (LLR), AIC and Deviance test were used to compare model fit and assess the contribution of different levels of variability. In bivariate analysis factors with p-value<0.2 were selected for inclusion in the multivariable multilevel logistics regression model. The final model provided the Adjusted Odds Ratios (AOR) with Corresponding 95% Confidence Intervals (CIs) to indicate the strength and directions of significance associations. Result The pooled prevalence of diarrhea and wasting co-occurrence (DW) among children aged 6−24 months in East Africa was 11% (95% CI: 10.8%−11.2%), with country-specific prevalence ranging from 3% in Zimbabwe to 17% in Malawi. Several factors were significantly associated with increased odds of DWM. Male children had an 84% higher risk of DWM (AOR 1.84; 95% CI: 1.69–2.02). Children born to mothers with no formal education (AOR 3.33; 95% CI: 2.30–4.81) or with primary (AOR 2.12; 95% CI: 1.59–2.74) or secondary education (AOR 1.47; 95% CI: 1.16–3.03) also had increased odds of DWM. Inadequate sanitation facilities, such as unimproved latrine facilities (AOR 1.47; 95% CI: 1.31–1.65) and unimproved water sources (AOR 1.47; 95% CI: 1.31–1.64), were similarly associated with higher odds of DWM. Additionally, not initiating breastfeeding in a timely manner was linked to increased odds of DWM (AOR 1.25; 95% CI: 1.10–1.41). Conversely, certain factors were associated with a reduced risk of DWM. Children living in rural areas had lower odds of DWM (AOR 0.85; 95% CI: 0.68–0.94). Additionally, children residing in Mozambique (AOR 0.59; 95% CI: 0.45–0.75) and Rwanda (AOR 0.57; 95% CI: 0.42–0.77) were less likely to experience DWM. Conclusion The study highlighted that the co-occurrence of diarrhea and wasting among children aged 6–24 months represents a significant public health issue in East African countries. To address this challenge, public health interventions focusing on improving maternal education, enhancing sanitation facilities, and promoting timely breastfeeding practices are essential for reducing the burden of diarrhea and wasting multimorbidity.